Residual symptoms in patients with partial versus complete remission of a major depressive disorder episode: patterns of painful physical symptoms in depression - Harada E (Dove Medical Press, 2016)
Eiji Harada,1 Yoichi Satoi,2 Toshiaki Kikuchi,3 Koichiro Watanabe,3 Levent Alev,1 Masaru Mimura4 1Medical Science, Medicines Development Unit-Japan, 2Statistical Science, Medicines Development Unit-Japan, Eli Lilly Japan K.K., Kobe, Hyogo, 3Department of Neuropsychiatry, Kyorin University School of Medicine, 4Department of Neuropsychiatry, Keio University School of Medicine, Tokyo, Japan Objective: The patterns of residual painful physical symptoms (PPS) and emotional symptoms among patients with partial remission (PR) or complete remission (CR) of a major depressive disorder (MDD) episode were compared. Methods: This is a multicenter, cross-sectional, observational study. Patients who had originally been diagnosed with MDD, were treated with an antidepressant for 12 weeks for that episode, and achieved either PR or CR at study entry were enrolled in the study. Using the 17-item Hamilton Rating Scale for Depression (HAM-D17), PR was defined as a score of ≥8 and ≤18 and CR as a score of ≤7. Residual symptoms were assessed using the Brief Pain Inventory-Short Form (BPI-SF) and the HAM-D17.Results: A total of 323 patients (CR =158, PR =165) were included in the study. Patients in the PR group had a higher mean (standard deviation) score in the HAM-D17 than those in the CR group (11.8 [3.1] and 4.4 [2.0], respectively). BPI-SF results showed that “at least moderate PPS” (score ≥3 on BPI-SF question 5) was significantly more prevalent among patients with PR than those with CR (37.0% vs 16.5%, respectively; odds ratio =3.04; P<0.001). Presence of pain (any severity) was also more prevalent among patients with PR than those with CR (54.5% vs 35.4%, respectively). The HAM-D17 results for individual items indicated that impaired work and activities, depressed mood, psychological and somatic anxiety, and general somatic symptoms were observed in at least 75% of patients with PR.Conclusion: PR was associated with a higher prevalence of at least moderate PPS. Other residual symptoms commonly observed in patients with PR included typical core emotional symptoms (eg, loss of interest, depressed mood, and psychological anxiety). These results underline the importance of PPS, because PPS is clinically relevant for the patients but difficult to assess with the commonly used depression evaluation scale.Keywords: major depressive disorder, residual symptoms, partial remission, complete remission, painful physical symptoms, pain, depression